Assessing preferences for mountain wine and viticulture by using a best-worst scaling approach: Do mountains really matter for Italians? - Mikael Oliveira Linder; Katia Laura Sidali; Christian Fischer; Valérie Bossi Fedrigotti; Diego Begalli; Gesa Busch (Wine Economics and Policy, 2022)
European Commission has recently published the rules on the use of the quality term "mountain product". The new regulation aims to promote the sustainable development of mountain areas and to facilitate the identification of mountain products by consumers. Despite the importance of viticulture for several European mountain communities and the growing interest of European consumers in quality certified foods, the regulation did not encompass wines. The literature addresses many issues regarding wines and consumer preferences, but so far mountain wines are not specifically researched. With this study, we seek to fill this gap by analysing Italian consumers' preferences for mountain wines as well as their opinion on the inclusion of this product in the mountain labelling scheme. To do so, this study applies a best-worst scaling model and subsequent latent class analysis. Data was collected through an online questionnaire applied to a consumer panel. The results indicate that most of respondents are in favour of applying the mountain label to wines. The three most preferred attributes are related to human health, ecological sustainability and product typicity. Most of the participants gave less importance to the attributes that characterize mountain agriculture. Only one consumer segment valued some of these. The findings suggest that the inclusion of mountain wines in the labelling scheme may increase the interest of Italian wine consumers, especially if health, sustainability and typicity are ensured by producers.
Keywords: 330; best-worst scaling; Italian preferences; latent class; mountain; viticulture; wine